(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
According to UNESCO (2020), school closures caused by the COVID-19 pandemic have affected over 1.5 billion students and families. The COVID-19 pandemic has presented multiple challenges for teaching students with disabilities in an online instructional environment, but there are also opportunities for collaboration, training, and communication for special educators to meet the needs of their students.